Perancangan dan Analisis Potensi Pembangkit Listrik Tenaga Mikro Hidro Di Aliran Sungai Brantas Sengkaling Kabupaten Malang Dalam Rangka Mencapai Target Energy Mix 23% Pada Tahun 2025 - Muhammad Helmi Kurniawan; Dovian Iswanda; Annisa Kesy Garside (Journal of Applied Mechanical Engineering and Renewable Energy, 2021)
A micro-hydropower plant is a small-scale power plant that uses water as its propulsion and the prime mover is a turbine. This generating system is very appropriate to be used in rural areas because this system is easy to manufacture, produces a large amount of electrical power, and is relatively inexpensive to manufacture. Based on the above, it is necessary to design a turbine that supports this generating system, including the Cross-Flow Turbine. To design a water turbine so that there are no errors in the design (such as the cost of making it), then a design is carried out. A cross-flow turbine design is designed with a flow rate (Q) = 1.2 m3/s, head (H) = 17 m with an efficiency of 0.75. The main technical specifications from the results of the turbine design are runner diameter (D) = 510 mm, turbine shaft rotation 471 rpm with a specific speed of 61.33 rpm, water power of 200,124 kW, and producing electric power of 100.86kW.